Applying Lean Kaizen to Improve Timely Computed Tomography Scan Appointments for Oncology Patients in a Safety Net Hospital. Issue 4 (17th April 2023) - Epistola, Raisa; Ho, Brian; Leong, Sally; Ali, Sana; Germono, Rachel; Kummerfeldt, Christopher; Gutierrez, Griselda; Shim, John; Lee, Jennifer M.; Yeh, James J.
Abstract : PURPOSE: Timely radiographic studies are essential to oncology care. At our institution, a safety net hospital in a large metropolitan area, baseline assessment determined that the overwhelming majority of outpatient computed tomographic (CT) scans for oncology patients were overdue and not scheduled within 2 weeks of their first requested date. METHODS: We conducted a series of structured, interdisciplinary meetings including staff from radiology, oncology, scheduling, and administration to critically review the scheduling process utilizing Lean Kaizen quality improvement methods. A new workflow was developed in which clinic staff scheduled CT scans before clinic discharge. Three months after our initial meeting, the new workflow was launched. We set a target of decreasing the percentage of overdue scans to below 20%. RESULTS: At baseline, 87% (65 of 75) of CT scans awaiting scheduling were overdue. Data were gathered at 5 and 10 weeks after implementation of our workflow. The percentage of CT scans overdue for scheduling was 17% (9 of 53) at 5 weeks and 0.97% (1 of 103) at 10 weeks after implementation. Clinic visit durations were not affected. CONCLUSION: The Lean Kaizen QI model was successful in decreasing the rate of oncology patients overdue for CT scan scheduling with minimal effects on clinic visit durations. This study demonstrated the importance of interdepartmental collaboration and continuous monitoring for improvement. Given the success of this project, this workflow will be expanded to other outpatient clinics within our institution.